Intraspecific alternative phenotypes contribute to variation in species’ strategies for growth - Samantha J. Worthy; María N. Umaña; Caicai Zhang; Luxiang Lin; Min Cao; Nathan G. Swenson (Oecologia, 2024)

Sources of bias in applying close‐kin mark–recapture to terrestrial game species with different life histories - Anthony Sévêque; Robert C. Lonsinger; Lisette P. Waits; Kristin E. Brzeski; Lisa M. Komoroske; Caitlin N. Ott‐Conn; Sarah L. Mayhew; D. Cody Norton; Tyler R. Petroelje; John D. Swenson; Dana J. Morin (Ecology, 2024)
Close‐kin mark–recapture (CKMR) is a method analogous to traditional mark–recapture but without requiring recapture of individuals. Instead, multilocus genotypes (genetic marks) are used to identify related individuals in one or more sampling occasions, which enables the opportunistic use of samples from harvested wildlife. To apply the method accurately, it is important to build appropriate CKMR models that do not violate assumptions linked to the species’ and population's biology and sampling methods. In this study, we evaluated the implications of fitting overly simplistic CKMR models to populations with complex reproductive success dynamics or selective sampling. We used forward‐in‐time, individual‐based simulations to evaluate the accuracy and precision of CKMR abundance and survival estimates in species with different longevities, mating systems, and sampling strategies. Simulated populations approximated a range of life histories among game species of North America with lethal sampling to evaluate the potential of using harvested samples to estimate population size. Our simulations show that CKMR can yield nontrivial biases in both survival and abundance estimates, unless influential life history traits and selective sampling are explicitly accounted for in the modeling framework. The number of kin pairs observed in the sample, in combination with the type of kinship used in the model (parent–offspring pairs and/or half‐sibling pairs), can affect the precision and/or accuracy of the estimates. CKMR is a promising method that will likely see an increasing number of applications in the field as costs of genetic analysis continue to decline. Our work highlights the importance of applying population‐specific CKMR models that consider relevant demographic parameters, individual covariates, and the protocol through which individuals were sampled.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Estimating benthic Fe and reactive solute fluxes - R.C. Aller; I.P. Dwyer; D.A. Swenson Perger; C. Heilbrun; N. Volkenborn; L.M. Wehrmann (Marine Chemistry, 2023)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Alternative designs and tropical tree seedling growth performance landscapes - Samantha J. Worthy; Daniel C. Laughlin; Jenny Zambrano; María N. Umaña; Caicai Zhang; Luxiang Lin; Min Cao; Nathan G. Swenson (Ecology, 2020)
The functional trait values that constitute a whole‐plant phenotype interact with the environment to determine demographic rates. Current approaches often fail to explicitly consider trait × trait and trait × environment interactions, which may lead to missed information that is valuable for understanding and predicting the drivers of demographic rates and functional diversity. Here, we consider these interactions by modeling growth performance landscapes that span multidimensional trait spaces along environmental gradients. We utilize individual‐level leaf, stem, and root trait data combined with growth data from tree seedlings along soil nutrient and light gradients in a hyper‐diverse tropical rainforest. We find that multiple trait combinations in phenotypic space (i.e., alternative designs) lead to multiple growth performance peaks that shift along light and soil axes such that no single or set of interacting traits consistently results in peak growth performance. Evidence from these growth performance peaks also generally indicates frequent independence of above‐ and belowground resource acquisition strategies. These results help explain how functional diversity is maintained in ecological communities and question the practice of utilizing a single trait or environmental variable, in isolation, to predict the growth performance of individual trees.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Does trait variation within broadly distributed species mirror patterns across species? A case study in Puerto Rico - María N. Umaña; Nathan G. Swenson (Ecology, 2019)
Although populations are phenotypically diverse, the majority of trait‐based studies have focused on examining differences among species. The justification for this broadly applied approach is based on the assumption that differences among species are always greater than within species. This is likely true for local communities, but species are often broadly distributed across a wide range of environments and patterns of intraspecific variation might surpass differences among species. Therefore, an appropriate interpretation of the functional diversity requires an assessment of patterns of trait variation across different ecological scales. In this study, we examine and characterize patterns of leaf trait variation for species that are broadly distributed along an elevational gradient. We focus on seven leaf traits that represent a main axis of functional differentiation in plants reflecting the balance between photosynthetic efficiency, display, and stomatal conductance. We evaluated patterns of trait variance across ecological scales (elevation, species, populations, and individuals) and examined trait covariance at both within species and across species levels, along the elevation gradient. Our results show three key patterns: (1) intraspecific leaf trait variation for broadly distributed species is comparable to the interspecific trait variation, (2) the trait variance structure is highly variable across species, and (3) trait coordination between pairs of leaf traits is evident across species along the gradient, but not always within species. Combined, our results show that trait coordination and covariance are highly idiosyncratic across broadly distributed and co‐occurring species, indicating that species may achieve similar functional roles even when exhibiting different phenotypes. This result challenges the traditional paradigm of functional ecology that assumes single trait values as optimal solutions for environments. In conclusion, patterns of trait variation both across and within species should be considered in future studies that assess trade‐offs among traits over environmental gradients.

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Evaluation of fluorophore-tethered platinum complexes to monitor the fate of cisplatin analogs - Justin C. Jagodinsky; Agnieszka Sulima; Yiqi Cao; Joanna E. Poprawski; Burchelle N. Blackman; John R. Lloyd; Rolf E. Swenson; Michael M. Gottesman; Matthew D. Hall (JBIC Journal of Biological Inorganic Chemistry, 2015)

Carbon Dynamics on the Louisiana Continental Shelf and Cross-Shelf Feeding of Hypoxia - Brian Fry; Dubravko Justić; Philip Riekenberg; Erick M. Swenson; R. Eugene Turner; Lixia Wang; Lora Pride; Nancy N. Rabalais; Janis C. Kurtz; John C. Lehrter; Michael C. Murrell; Elizabeth H. Shadwick; et al. (Estuaries and Coasts, 2015)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Paleo‐indicators and water quality change in the Charlotte Harbor Estuary (Florida) - R. E. Turner; N. N. Rabalais; B. Fry; N. Atilla; C. S. Milan; J. M. Lee; C. Normandeau; T. A. Oswald; E. M. Swenson; D. A. Tomasko (Limnology and Oceanography, 2006)
We reconstructed water quality changes for 1800 to 2000 in Charlotte Harbor (Florida), a shallow subtropical estuary, by using a suite of biological and geochemical proxies in dated sediments collected in the region of a present day, midsummer hypoxic zone. The declining freshwater loading into the estuary from 1931 to the 1980s is not the probable causal agent encouraging the appearance or expansion of a hypoxia zone (measuring up to 90 km 2 in summer). Rather, the reconstructed trends in nitrogen loading indicate increased phytoplankton production has likely caused a decline in bottom water oxygen concentrations. Sedimentary biogenic silica (BSi), carbon, nitrogen, and phosphorus concentrations increased concurrently with known or inferred changes in nutrient loadings. There were direct relationships between phytoplankton pigments and BSi, heavier δ 34 S with increased carbon loading, and sequestration of P, Al, and Fe as carbon loading increased. The results from the sediment analyses and the results from mixing models using C:N ratios and δ 13 C suggest an estuarine system that is responsive to increased carbon loading from the nitrogen‐limited phytoplankton community and whose sediments are becoming increasingly anoxic as a result. The present nitrogen loading is about three times above that prior to the 1800s, suggesting that without management intervention the anticipated doubling of the watershed’s population from 1990 to 2020 will greatly increase the nitrogen loading to this estuary and will lead to much higher amounts of phytoplankton biomass and accumulation and exacerbate hypoxic conditions.

Inhibition of antagonist and agonist binding to the human brain muscarinic receptor by arachidonic acid - Jacob R. Kjome; Kathryn A. Swenson; Melissa N. Johnson; Elizabeth Z. Bordayo; Lisa E. Anderson; Lars C. Klevan; Ada I. Fraticelli; Steven L. Aldrich; John R. Fawcett; Homer D. Venters; Thomas A. Ala; William H. Frey (Journal of Molecular Neuroscience, 1998)